Hepatitis C Virus Seroconversion among Hiv-Positive Men Who Have Sex with Men with No History of Injection Drug Use: Results from a Clinical Hiv Cohort - Ann N Burchell; Sandra L Gardner; Tony Mazzulli; Michael Manno; Janet Raboud; Vanessa G Allen; Ahmed M Bayoumi; Rupert Kaul; Frank McGee; Peggy Millson; Robert S Remis; Wendy Wobeser; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Internationally, there is a growing recognition that hepatitis C virus (HCV) may be sexually transmitted among HIV-positive men who have sex with men (MSM).